2018
DOI: 10.1039/c7nr08035b
|View full text |Cite
|
Sign up to set email alerts
|

p-Type conductivity of hexagonal boron nitride as a dielectrically tunable monolayer: modulation doping with magnesium

Abstract: Hexagonal boron nitride (h-BN) is the widest band gap 2D material (>6 eV), which has attracted extensive attention. For exploring potential applications in optoelectronic devices, electrical conductivity modulation (n or p type) is of extreme importance. Here, we report the achievement of a large-scale and high quality h-BN monolayer with p-type conductivity by modulation doping of Mg using a low pressure chemical vapor deposition method. A large-scale monolayer h-BN (>10 inches) was grown by using a wound Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…At room temperature, the resistivity of the sample with the highest doping (D) was 2 × 10 4 Ω•cm, with a doping concentration of 5 × 10 15 cm −3 . These values can be compared to those obtained by Sun et al [20] who reported a resistivity and doping concentration of 1.2 × 10 −5 Ω•cm and of 1.7 × 10 14 cm −2 , respectively, for an h-BN monolayer grown on Cu foil and transferred on SiO 2 . For a thicker layer of h-BN (300 nm), the reported resistivity and doping concentration are 2.3 Ω•cm and 1.1 × 10 18 cm −3 [7,8], respectively.…”
Section: Ohmic Contact In H-bn Layerssupporting
confidence: 52%
See 2 more Smart Citations
“…At room temperature, the resistivity of the sample with the highest doping (D) was 2 × 10 4 Ω•cm, with a doping concentration of 5 × 10 15 cm −3 . These values can be compared to those obtained by Sun et al [20] who reported a resistivity and doping concentration of 1.2 × 10 −5 Ω•cm and of 1.7 × 10 14 cm −2 , respectively, for an h-BN monolayer grown on Cu foil and transferred on SiO 2 . For a thicker layer of h-BN (300 nm), the reported resistivity and doping concentration are 2.3 Ω•cm and 1.1 × 10 18 cm −3 [7,8], respectively.…”
Section: Ohmic Contact In H-bn Layerssupporting
confidence: 52%
“…Furthermore, when compared to the peak position of sample A (25.86 • ), a shift of the (002) peak was observed in sample B (25.72 • ). This may be related to the deformation of the surrounding lattice because of the difference of atom sizes between B and Mg [20]. However, the peak shift at the lower angle was not observed in samples C and D. This is related to the formation of an accumulation of disordered phases in samples C and D, which overcomes the effect of Mg incorporation.…”
Section: Morphology and Structural Characterizations Of Undoped And Mg Doped H-bn Layersmentioning
confidence: 86%
See 1 more Smart Citation
“…It is known that the high quality free-standing ML hBN is normally weakly conducting [14]. Similar to conventional semiconductor based devices, ML hBN based electronic and optoelectronic devices are often placed on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These properties mean that h-BN is a promising candidate material for use as a p-type layer in optical devices. There have been a number of reports of h-BN layer synthesis using chemical vapor deposition (CVD) methods [16][17][18][19]. In these studies, the favored substrate materials are mostly metals such as Ni, Cu, or Fe, which are used as catalytic layers to promote h-BN film formation.…”
Section: Introductionmentioning
confidence: 99%